Nature of domestic/family violence and barriers to using services among Indian immigrant women - Colucci, Erminia; O’Connor, Manjula; Field, Karen; Baroni, Alice; Pryor, Reima; Minas, Harry (Alterstice, 2013)
Domestic/family violence is a widespread major public health and human rights violation issue that runs across ethno-cultural affiliations and economic status. Relative to the actual incidence of family violence, use of services is low, and delayed for years after onset, within the broader Victorian and Australian community. Utilization is even lower for women from immigrant and refugee communities. It has been noted that family violence service utilization by Indian women immigrants in particular was especially low, relative to the size of the Indian population in Victoria. With the Indian culture understood to be traditionally a strongly male-dominated culture, it was deemed important to explore the nature of family violence experience of Indian women living in Australia, and culturally determined barriers to use of services. A partnership was formed to explore this issue through a participatory community theatre approach.Forum Theatre is a powerful tool that uses theatre for generating community understanding around hard to address issues such as domestic violence. Using such theatre-based ethnography, we aimed to identify the key issues, challenges and needs of Indian immigrant families when accessing and using services that could assist in situations of domestic/family violence.